Innovative low-cost fogging for dengue mosquito eradication and clean living space - Putra, Afdhol Aulia; Wulandari, Meli; Yudasmara, Damar; Mariani, Dini (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Dengue fever, caused by the Aedes aegypti mosquito, remains a significant public health challenge in tropical regions. Traditional fogging methods for mosquito eradication often require substantial resources, making them less accessible to low-income communities. This study introduces an innovative, low-cost fogging technology designed to effectively target dengue-carrying mosquitoes while promoting sustainable, clean-living spaces. The proposed system utilizes readily available materials and environmentally friendly substances to create a cost-effective and efficient fogging mechanism. Field trials demonstrate the technology's efficacy in reducing mosquito populations and improving hygiene conditions in targeted areas. By integrating community involvement and simple operational guidelines, this approach bridges the gap between resource limitations and the need for effective vector control. The findings highlight the potential for widespread adoption, particularly in underserved regions, contributing to both public health improvement and enhanced living standards